2018
DOI: 10.14488/bjopm.2018.v15.n4.a12
|View full text |Cite
|
Sign up to set email alerts
|

Lean Office and digital transformation: a case study in a services company

Abstract: - Highlights: a high percentage of the Western world workforce works in offices; Value Stream Map, a lean tool, allows waste identification in services companies; Lean Management helps companies to prepare for digital transformation; there is scarce scientific literature ondigital transformation and Lean Office. -Goal: thepurpose of this article is to report the implementation of Lean Office and digital transformation in a services company. - Design / Methodology / Approach: the research method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Entre las aplicaciones de LO desde la perspectiva de servicios en las empresas destacan la optimización de los costos administrativos (Bracci, 2013), el diseño de unidades bancarias de empresas del sector financiero en donde lograron una reducción de tiempo de proceso del 45% (Calsavara, 2016), la mejora de la eficiencia del procesamiento de datos y por tanto de las operaciones de un departamento logístico que se encarga del suministro de materias primas en una empresa de componentes multimedia para automóviles (Monteiro et al, 2017), el uso de LO en la transformación digital de empresas de servicios de IoT o internet de las cosas (Besser Freitag, 2018), la reducción de gastos de impresión y papelería en un departamento de facturación de una empresa de servicios de electricidad (Almeida et al, 2019) y en el proceso de capacitación de su personal gerencial en un proceso de restructuración (Ribeiro et al, 2019), y la eliminación de desperdicios en el proceso de separación de materiales en el almacen de una empresa del sector energético para mejorar el suministro en las estaciones de trabajo (dos Santos et al, 2021).…”
Section: Lean Office Aplicado En Empresas De Serviciounclassified
“…Entre las aplicaciones de LO desde la perspectiva de servicios en las empresas destacan la optimización de los costos administrativos (Bracci, 2013), el diseño de unidades bancarias de empresas del sector financiero en donde lograron una reducción de tiempo de proceso del 45% (Calsavara, 2016), la mejora de la eficiencia del procesamiento de datos y por tanto de las operaciones de un departamento logístico que se encarga del suministro de materias primas en una empresa de componentes multimedia para automóviles (Monteiro et al, 2017), el uso de LO en la transformación digital de empresas de servicios de IoT o internet de las cosas (Besser Freitag, 2018), la reducción de gastos de impresión y papelería en un departamento de facturación de una empresa de servicios de electricidad (Almeida et al, 2019) y en el proceso de capacitación de su personal gerencial en un proceso de restructuración (Ribeiro et al, 2019), y la eliminación de desperdicios en el proceso de separación de materiales en el almacen de una empresa del sector energético para mejorar el suministro en las estaciones de trabajo (dos Santos et al, 2021).…”
Section: Lean Office Aplicado En Empresas De Serviciounclassified
“…Despite the growing acknowledgment of the significance of lean principles and digital transformation within the service industry, a discernible gap persists in the existing body of knowledge. While previous studies have delved into either lean practices or digital transformation individually, there remains a shortage of comprehensive research exploring the synergistic effects arising from the integration of lean principles with digital transformation in service organizations [13] . This study endeavours to address this gap by providing a holistic examination of how the convergence of lean principles and digital transformation can contribute to waste reduction in the operational service industry [14].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Research focused on a group of hospitals in Malaysia identified that they did not have standardized processes, so there were waste and long waiting times in care processes [6]. Following this same line, A case study was developed in an IoT solutions provider located in Brazil, and it was able to demonstrate how the implementation of Lean principles, techniques and tools can bring benefits to the Operations department in reducing waiting times [7].…”
Section: Introductionmentioning
confidence: 99%